De novo transcriptome assembly and identification of salt-responsive genes in sugar beet M14. (August 2018) - Lv, Xiaoyan; Jin, Ying; Wang, Yuguang
Graphical abstract: Highlights: A reference transcriptome dataset of sugar beet M14 was generated using RNAseq technology. Differentially expressed genes in the sugar beet M14 leaves and roots under salt stress were analyzed. QRT-PCR approach was used to validate changes in transcript levels of sugar beet M14 under salt. Abstract: Sugar beet ( Beta vulgaris ) is an important crop of sugar production in the world. Previous studies reported that sugar beet monosomic addition line M14 obtained from the intercross between Beta vulgaris L. (cultivated species) and B. corolliflora Zoss (wild species) exhibited tolerance to salt (up to 0.5 M NaCl) stress. To estimate a broad spectrum of genes involved in the M14 salt tolerance will help elucidate the molecular mechanisms underlying salt stress. Comparative transcriptomics was performed to monitor genes differentially expressed in the leaf and root samples of the sugar beet M14 seedlings treated with 0, 200 and 400 mM NaCl, respectively. Digital gene expression revealed that 3856 unigenes in leaves and 7157 unigenes in roots were differentially expressed under salt stress. Enrichment analysis of the differentially expressed genes based on GO and KEGG databases showed that in both leaves and roots genes related to regulation of redox balance, signal transduction, and protein phosphorylation were differentially expressed. Comparison of gene expression in the leaf and root samples treated with 200 and 400 mM NaCl revealed different mechanisms for coping with salt stress. In addition, the expression levels of nine unigenes in the reactive oxygen species (ROS) scavenging system exhibited significant differences in the leaves and roots. Our transcriptomics results have provided new insights into the salt-stress responses in the leaves and roots of sugar beet.